La papa como ventaja competitiva - Cárdenas Núñez, Gilberto José Rafael (2009)
Food production and population growth are a source of analysis and discussion among practitioners and academics even more in the first decade of XXI century, when the new criteria differ due to technological advances, in this case biotechnology, genetic engineering and transgenesis in particular. The Peruvian territory is as much potato species known worldwide. Currently in Peru, is the main crop in acreage and accounts for 25% of agricultural GDP. Is the staple food of the Andean region and is produced by 600 000 small agricultural units. Is a product that contains 100 grams, 78 grams moisture, 18.5 gr. starch and is rich in potassium (560 mg) and vitamin C (20 mg).